Theory and method in higher education research - Tight, Malcolm; Huisman, Jeroen (Bingley, U.K. : Emerald, 2013)
Theory and method in higher education research contains contemporary contributions to international debates regarding the application and development of theory and methodology in researching higher education. Higher education research is a developing field internationally, which is attracting more and more researchers from a great variety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories, methods and methodologies is being applied. As an expanding multidisciplinary area of interest, we may also expect increased development of theory and method. This volume aims to offer a channel for discussion, critique and innovation. It should become essential reading for the growing numbers of researchers engaging with higher education across the globe.
Comparative research in higher education studies : considering the different levels of comparison and emerging methodological challenges / Lorenza Antonucci -- Policy research in higher education : theories and methods for globalising times / Lesley Vidovich -- The critical higher education policy discourse analysis framework / David Hyatt -- Critical discourse analysis and higher education research / Karen Smith -- Discourse analysis in higher education research / Sofia Branco Sousa, António Magalhães -- Tracking experience over time : epistemological issues and methodological challenges / Lynn McAlpine, Cheryl Amundsen, Gill Turner -- Identity as a theoretical construct in research about academic careers / Meghan Pifer, Vicki Baker -- Addressing challenges of conducting quality mixed methods studies in higher education / Antigoni Papadimitriou, Nataliya Ivankova, Sylvia Hurtado -- Methods on the margins? Queer theory as method in higher education research / Vicky Gunn, Chris McAllister -- Within/against : feminist theory as praxis in higher education research / Jill Blackmore -- Visualising knowledge structures to highlight the articulation between theory and method in higher education research / Ian M. Kinchin -- Using structural equation modelling to understand predictors of undergraduate students academic performance / Paul Sander, David Putwain, Jesús de la Fuente -- Phenomenography : from critical aspects to knowledge claim / Brandon Collier-Reed, Åke Ingerman -- An application of variation theory of learning in higher education / Airi Rovio-Johansson.
Print version record
Keywords: Education -- Higher; Education -- Aims & Objectives; Higher & further education, tertiary education; Research methods: general; Education, Higher -- Research; Education, Higher -- Research -- Methodology